Malignant Infantile Osteopetrosis: A Rare Genetic Disorder - Aya Mohammed Alsabbah; Mohammed Ali Alsabbah; Mahmoud Ahmed Radaideh; Shafeeka Mohmed Saleh; Rawan Ahmed Mehanna (Dubai Medical Journal, 2024)
Introduction: Osteopetrosis is a clinical syndrome characterized by impairment in the production or function of osteoclasts, leading to bone condensation. Symptoms and their onset depend on the disease’s hereditary pattern.